Strong and Weak Light-Matter Interactions in Plasmonic and Optical Cavities - Polat, Nahit; Polat, Nahit; Balcı, Sinan (01. Izmir Institute of Technology, 2023)
This thesis investigates the interaction of light and matter through both experimental and theoretical approaches, focusing on two key topics: Strong and Weak coupling. We also examine the field of strong light-matter interactions under two headings: plasmonic and optical cavities. In the section on plasmonic cavities, we focus on the strong coupling between surface plasmon polaritons and excitons with different optical properties and localized surface plasmon resonance. We also discuss the strong coupling between localized surface plasmon resonance and excitons in plasmonic nanoparticles with different optical properties due to their different shapes. This thesis focuses on the theoretical and optical characterization of the aforementioned topics. Therefore, details on the manufacturing processes are not given. Instead, it presents a comparative analysis of optical measurement results and related simulation data, to which I have contributed more. In addition, we demonstrate for the first time hyperspectral imaging of exciton polaritons at optical microcavities. Two metal thin films acting as reflectors and a polymer matrix containing a collection of quantum emitters form the hybrid system for polariton imaging. We show a strong exciton-photon interaction between photons trapped in the microcavity and Frenkel excitons of dye molecules placed inside the optical microcavity. We find that exciton polaritons in the optical microcavity can be imaged and spatially mapped using hyperspectral imaging in the visible region. In the field of weak light-matter interactions, the focus of the thesis is on the Fano resonance, which is a unique case in the weak coupling regime. The degree of coupling between interacting systems plays a critical role in determining the extent to which constructive and destructive interference phenomena occur in the system. An important example of destructive interference is the Fano resonance, which is caused by interference between two optical paths that are characterized by different states: one is narrow and discrete, and the other is broad and continuum. This is the first study to theoretically investigate the destructive interference between subwavelength excitonic nanoparticles placed on the surface of a prism for Fano resonance observations and the evanescent wave scattering on the prism surface. In an attempt to understand the intricate dynamics between the evanescent wave and the Fano resonance, we study the effect of changing the angle of incidence of the incident plane wave on the properties of the Fano resonance. Furthermore, we also investigate how the size of the excitonic nanoparticles and the absorption linewidth influence the properties of the Fano resonance.

Bu tez, ışık ve maddenin etkileşimini hem deneysel hem de teorik yaklaşımlarla araştırmakta ve iki temel konuya odaklanmaktadır: Güçlü ve Zayıf etkileşme. Güçlü ışıkmadde etkileşimleri alanını da iki başlık altında inceliyoruz: Plazmonik ve Optik Boşluklar. Plazmonik kaviteler bölümünde, yüzey plazmon polaritonları ile farklı optik özelliklere sahip eksitonlar ve lokalize yüzey plazmon rezonansı arasındaki güçlü eşleşmeye odaklanıyoruz. Ayrıca, farklı şekilleri nedeniyle farklı optik özelliklere sahip plazmonik nanoparçacıklardaki yerelleştirilmiş yüzey plazmon rezonansı ile eksitonlar arasındaki güçlü etkileşmeyi de tartışıyoruz. Bu tez, yukarıda bahsi geçen konuların teorik ve optik karakterizasyonuna odaklanmaktadır. Bu nedenle, üretim süreçleriyle ilgili ayrıntılar verilmemiştir. Bunun yerine, çalışma optik ölçüm sonuçlarının ve ilgili simülasyon verilerinin karşılaştırmalı bir analizini sunmaktadır. Bunun yerine, daha çok katkımın bulunduğu optik ölçüm sonuçlarının ve ilgili simülasyon verilerinin karşılaştırmalı bir analizini sunmaktadır. Buna ek olarak, optik mikrokavitelerde eksiton polaritonların hiperspektral görüntülemesini ilk kez gösteriyoruz. Yansıtıcı görevi gören iki metal ince film ve bir kuantum yayıcı koleksiyonu içeren bir polimer matris, polariton görüntüleme için hibrit sistemi oluşturuyor. Mikro boşlukta hapsolmuş fotonlar ile optik mikro boşluk içine yerleştirilmiş boya moleküllerinin Frenkel eksitonları arasında güçlü bir eksiton-foton etkileşimi olduğunu gösteriyoruz. Optik mikro boşluktaki eksiton polaritonlarının görünür bölgede hiperspektral görüntüleme kullanılarak görüntülenebileceğini ve uzamsal olarak haritalanabileceğini bulduk. Zayıf ışık-madde etkileşimleri alanında, tezin odak noktası zayıf bağlaşım rejiminde benzersiz bir durum olan Fano rezonansıdır. Etkileşen sistemler arasındaki bağlantı derecesi, sistemde yapıcı ve yıkıcı girişim olaylarının ne ölçüde meydana geldiğinin belirlenmesinde kritik bir rol oynar. Yıkıcı girişimin önemli bir örneği, farklı durumlarla karakterize edilen iki optik yol arasındaki girişimin neden olduğu Fano rezonansıdır: biri dar ve ayrık, diğeri geniş ve süreklidir. Bu çalışma, Fano rezonans gözlemleri için bir prizmanın yüzeyine yerleştirilen alt dalga boylu eksitonik nanoparçacıklar ile prizma yüzeyindeki evanesant dalga saçılımı arasındaki yıkıcı girişimi teorik olarak araştıran ilk çalışmadır. Evanesant dalga ve Fano rezonansı arasındaki karmaşık dinamikleri anlamak amacıyla, gelen düzlem dalganın geliş açısını değiştirmenin Fano rezonansının özellikleri üzerindeki etkisini inceliyoruz. Ayrıca, eksitonik nanoparçacıkların boyutunun ve soğurma çizgi genişliğinin Fano rezonansının özelliklerini nasıl etkilediğini de araştırıyoruz.
Plazmonik ve optik kavitelerde güçlü ve zayıf ışık madde etkileşimleri
Thesis (Doctoral)--İzmir Institute of Technology, Photonics, Izmir, 2023
Includes bibliographical references (leaves. 50-57)
Text in English; Abstract: Turkish and English.
Keywords: Plasmons (Physics); Surfaces (Physics); Surface plasmon resonance.; Electromagnetic measurements; Optics.; Light; Photonics; Electromagnetic coupling; Silver nanoparticles; Microcavity